Liquid–liquid equilibrium in polymer–fullerene mixtures; an in situ neutron reflectivity study - Elizabeth Hynes (Soft Matter, 2020)
The composition profiles of a series of model polystyrene/fullerene bilayers are measured, before, during and after thermal annealing, using in situ neutron reflectometry. In combination with grazing-incidence X-ray diffraction measurements, these experiments, which quantify layer compositions as a function of molecular weight using changes in both scattering length density and layer thickness, extend and corroborate recent measurements on ex situ annealed samples and demonstrate that the composition profiles rapidly formed in these systems correspond to two co-existing liquid–liquid phases in thermodynamic equilibrium. The measurements also demonstrate a clear and systematic onset temperature for diffusion of the fullerenes into the PS layer that correlates with the known glass-transition temperatures of both the polymer (as a function of molecular weight) and the fullerene, revealing that the molecular mobility of the fullerenes in these systems is controlled by the intrinsic mobility of the fullerenes themselves and the ability of the polymer to plasticise the fullerenes at the interface. Over the temperature range investigated (up to 145 °C), measurements of equilibrated composition profiles as a function of temperature (during gradual cooling) reveal no significant changes in composition profile, other than those associated with the known thermal expansion/contraction of polystyrene thin-films.